The Kennedy center ([s.l] : Stagebill, 1998)
This file includes a booklet describing different play actors, posit ions held in the play and names used. It also includes a document titl ed stepping stones and the SS (stepping stones) training and adaptation project.
AR/SIC/3/8
English
Shelf no. 3
Keywords: Literature